O Canto que Virou Património: da “Beleza Do Morto” aos Futuros Possíveis - Simões, Dulce (Trabalhos de Antropologia e Etnologia, 2020)
“Popular culture”, has been invoked as a magic formula whose effect would be sufficient to guarantee the existence of reality (Revel 1989), and it is presented to us in an authoritative and up-to-date version of Intangible Cultural Heritage. In this text I discuss the patrimonialization processes as reproductions of modalities of holism applied to the collective that today occupy the place of what the folkorists of the past understood as the “people”, from an ethnographic study conducted in the border of Baixo Alentejo, complemented by bibliographic and documentary sources. This is a first approach to issues related to the (re) production of the symbolic imaginary of Cante Alentejano, carried out within two research projects.